MANAGEMENT OF COMPETITIVE POSITIONS OF THE ENTERPRISE - SHPILEVA, VIRA; KRAVCHYK, YURII; YASHCHENKO, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article focuses on the management of competitive positions of the enterprise, in particular, analyzed and developed a number of proposals on the example of financial and economic and management activities of the enterprise, which specializes in providing construction and repair services.The purpose of the article is to substantiate the new methodological and applied principles of evaluation and policy formation to improve the competitive position of the enterprise.Modern scientific research in the field of managing competitive positions of enterprises is analyzed and it is concluded that constant change of business conditions, high dynamics of changes in market conditions and market positions of enterprises, emergence of new methods and valuation methods and strategies for competitiveness require new theoretical and methodological developments in terms of improving the management system of competitive positions of the enterprise.A method of comprehensive analysis of the competitive position of the company, including analysis of investment attractiveness of the industry, calculation of the structure and dynamics of the Herfindahl-Hirschman index, the dynamics of the capacity of the target market segment in which the company specializes. The method of compiling a competitive map of competing companies in the market of construction and repair services in the region has been developed and tested. The matrix "Level of attractiveness of the industry in which the company operates" is proposed, calculated and built according to the criteria: (1) the intensity of competition in the industry; (2) stage of development of the industry.The applied significance of the research results is that priority measures have been identified to strengthen such components of enterprise competitiveness as financial, intellectual and personnel, technical and technological and others.The scientific novelty of the research results is the substantiation of new methodological approaches to the analysis of the competitive position of the enterprise in the market.
Keywords: competitiveness; competitive positions; market research; enterprise; cost management; strategic development